2020
DOI: 10.3390/ijms21082702
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Platelet-Rich Plasma Use in Androgenetic Alopecia Compared with Minoxidil®, Finasteride®, and Adult Stem Cell-Based Therapy

Abstract: The number of articles evaluating platelet-rich plasma (PRP) efficacy in androgenic alopecia (AGA) have exponentially increased during the last decade. A systematic review on this field was performed by assessing in the selected studies the local injections of PRP compared to any control for AGA. The protocol was developed in accordance with the Preferred Reporting for Items for Systematic Reviews and Meta-Analyses-Protocols (PRISMA-P) guidelines. A multistep search of the PubMed, MEDLINE, Embase, PreMEDLINE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 72 publications
1
103
0
9
Order By: Relevance
“…A randomized clinical trial demonstrated that the microinjection of adipose-derived mesenchymal stem cells (AD-MSCs) and stromal vascular fraction cells (SVFs) can stimulate the scalp epidermal stem cells and hair growth in androgenic alopecia patients. However, in many of these patients, frequent microinjection is required to sustain the hair growth [ 10 ]. Thus, novel therapies for hair loss treatment has long been sought.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized clinical trial demonstrated that the microinjection of adipose-derived mesenchymal stem cells (AD-MSCs) and stromal vascular fraction cells (SVFs) can stimulate the scalp epidermal stem cells and hair growth in androgenic alopecia patients. However, in many of these patients, frequent microinjection is required to sustain the hair growth [ 10 ]. Thus, novel therapies for hair loss treatment has long been sought.…”
Section: Introductionmentioning
confidence: 99%
“…One of the problems most frequently raised by the scientific international audience is the level of consolidated evidence-based medicine (EBM) offered by PRP in the in vivo treatment of soft/bone tissue defects [ 10 , 11 , 45 , 48 , 50 ], aesthetic defects [ 55 ], wound healing [ 46 , 47 , 56 , 57 ] and hair loss [ 5 , 6 , 7 , 58 , 59 , 60 , 61 ] compared versus FDA-approved and/or EMA/CAT and/or other institutions. The rationale of this problem is borne by the fact that many institutional guidelines of several nations are based on the EBM impact of a drug/procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In all enrolled studies, calcium gluconate at a 10:1 ratio and sodium citrate were mostly added as activators and anticoagulants, respectively. Moreover, platelet concentrations differed from 1.5 to 7 times as much as the whole blood, according to PRP preparation protocols [52,58].…”
Section: Platelet-rich Plasma Preparationmentioning
confidence: 99%
“…Alternatively, the use of autologous platelet-derived growth factors, contained in PRP, may represent a valid regenerative strategy for their capacity to promote cell proliferation, differentiation, and neo-angiogenesis, favoring, in vivo, the WH process [52], and hair regrowth (HR) has been reported recently [53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%